Reverse advance internal magnesium diffusion process to produce dense MgB2 bulks and high JC wires through high pressure heat treatment. (2nd November 2020) - Bovone, G; Capra, M; Bernini, C; Loria, F; Cetner, T; Gajda, D; Morawski, A; Ballarino, A; Hopkins, S C; Tropeano, M; Grasso, G; Putti, M; et al.
Abstract: Here we report a new versatile technique to manufacture MgB2 massive samples, called reverse advance internal magnesium diffusion (r-AIMI). The idea focuses on the goal of obtaining dense bulk or wire samples depending on synthesis conditions. In respect to the traditional AIMI procedure, in which a central Mg rod is covered with a B corona, here a Mg tube is filled with B powder and clad in a Ti external sheath, which is quite similar to the traditional (powder in tube) technique. After cold deformation, during which several intermediate low temperature heat treatments are necessary in order to relax the Ti sheath and Mg tube, samples are reacted at high temperature and ambient pressure to form a dense MgB2 core. The MgB2 phase results are totally disconnected from metallic sheath, and can be easily extracted and characterized. Critical current density measurements show values exceeding 10 6 A cm −2 below 1.5 T at 20 K. In the last part of the paper, we show the effect of final heat-treatment performed under high pressure to eliminate the present void and connect the external sheath to the internal MgB2 core and so permitting the electric transfer necessary for power applications of wires.